O uso de si ao extremo: um olhar sobre as vivências de sofrimento de trabalhadores afastados por LER/Dort - Peixoto, Julliana Diniz (2021)
This dissertation aims to analyze the experiences of suffering of workers in work leave situation affected by some pathology related to RSI / WMSD. To achieve this goal, the study is organized first with the presentation of a theoretical chapter using the Psychodynamics of work as bases. Following is a first article that comprises a review of the bibliography on experiences of suffering and RSI / WMSD, in Scielo, Lilacs and Index Psi databases. From the analysis of the sample articles, it was possible to observe three dimensions with regard to musculoskeletal disorders: the physical dimension, the psychosocial dimension and the relationship between work organization and illness. The second study presents itself as a qualitative research carried out through telephone interviews, with five workers in a work leave situacion, affected by RSI / WMSD, and users of the Reference Center for Occupational Health of João Pessoa (CEREST-JP). From the reports, it was possible to observe that the worker in work leave situacion due to this syndrome faces, in addition to physical pain, feelings of guilt, worthlessness and uncertainties about the future. The subjective dimension is a key factor in illness and contributes to the experiences of both physical and psychological suffering of workers. RSI / WMSD are one of the biggest causes of workers' removal from their jobs. It is in this perspective that the importance of studies at the experiences of suffering of workers in work leave situation due to RSI / WMSD is understood.